Legal Non-Compliance and Kiai Hegemony: The Practice of Unregistered Marriages among the Madurese Muslim Community of Kubu Raya - Baihaqi, Baihaqi; Tutik, Titik Triwulan; Musadad, Ahmad; Khazin, A. Mufti; Simun, Mahtumridho Ghufron bin (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
The practice of unregistered marriages (nikah siri) in traditional Muslim communities is often seen as non-compliance with state regulations. However, this behaviour cannot be understood without considering the influence of kiai (local religious leader) in the public sphere. This article explores the dynamics of unregistered marriage practices within the Madurese Muslim community of Kubu Raya, West Kalimantan, Indonesia. Employing a socio-legal research framework, the study collects data through in-depth interviews with 25 key informants, including widowed couples engaged in unregistered marriages, kiai, village officials, and community leaders. Drawing on Peter L. Berger’s theory of the social construction of reality, this article analyses the relationship between those involved in unregistered marriages and the hegemony of kiai. The study finds that unregistered marriages in the Madurese Muslim community are influenced by the kiai’s view that a marriage contract meeting the conditions of Islamic jurisprudence (fiqh) is valid without registration at the local Religious Affairs Office. This practice represents a social reality legitimised by religious authority. For the Madurese Muslim community, the religious legitimacy conferred by the kiai serves as a basis of faith, prompting them to engage in unregistered marriages despite this practice conflicting with state law. The article highlights the dominant role of kiai in shaping social realities that may diverge from compliance with state law in traditional Muslim communities. [Praktik perkawinan yang tidak dicatatkan (nikah siri) pada komunitas muslim tradisional sering kali dinilai sebagai ketidakpatuhan mereka terhadap regulasi administratif yang diatur oleh negara. Namun, perilaku tersebut tidak dapat dipisahkan dari pengaruh hegemoni para kiai di ruang publik. Artikel ini mengkaji dinamika praktik nikah siri yang dilakukan oleh komunitas muslim Madura di Kubu Raya, Kalimantan Barat, Indonesia. Artikel ini merupakan penelitian sosio-legal dengan menggunakan teknik pengumpulan data melalui wawancara mendalam terhadap 25 informan kunci yang terdiri dari para pasangan nikah siri yang berstatus sebagai duda dan janda, kiai, perangkat desa, dan tokoh masyarakat. Dengan menggunakan teori konstruksi sosial atas kenyataan dari Peter L. Berger untuk mengeksplorasi hubungan dialektis antara pelaku nikah siri dan hegemoni kiai, artikel ini menemukan bahwa nikah siri yang dipraktikkan oleh komunitas muslim Madura dipengaruhi oleh pandangan kiai bahwa akad nikah yang telah memenuhi syarat dan rukun perkawinan dalam fikih adalah sah, tanpa perlu mencatatkannya di kantor urusan agama setempat. Praktik ini merupakan bentuk kenyataan sosial yang telah mendapatkan legitimasi keagamaan dari kiai. Bagi masyarakat muslim Madura, legitimasi keagamaan yang diberikan oleh kiai menjadi modal keyakinan bagi mereka untuk melakukan nikah siri, meskipun perilaku tersebut bertentangan dengan hukum administrasi negara. Temuan ini menunjukkan bahwa hegemoni kiai yang dominan dalam kehidupan sehari-hari masyarakat muslim tradisional dapat mengonstruksi kenyataan sosial yang tidak taat terhadap hukum negara.]